2014
DOI: 10.1093/infdis/jiu673
|View full text |Cite
|
Sign up to set email alerts
|

BrucellaIntracellular Life Relies on the Transmembrane Protein CD98 Heavy Chain

Abstract: Brucella are intracellular bacterial pathogens that use a type IV secretion system (T4SS) to escape host defenses and create a niche in which they can multiply. Although the importance of Brucella T4SS is clear, little is known about its interactions with host cell structures. In this study, we identified the eukaryotic protein CD98hc as a partner for Brucella T4SS subunit VirB2. This transmembrane glycoprotein is involved in amino acid transport, modulation of integrin signaling, and cell-to-cell fusion. Knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Trophoblastic functions are tightly controlled, and defects may lead to severe complications during pregnancy. Interestingly, several of these functions involve CD98hc, which we found to be essential for Brucella infection of other cell types (Keriel et al, 2015). CD98hc (SLC3A2) is a surface glycoprotein mediating amino-acid transport, regulation of integrin-dependent signalling and cell fusion (Nguyen & Merlin, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…Trophoblastic functions are tightly controlled, and defects may lead to severe complications during pregnancy. Interestingly, several of these functions involve CD98hc, which we found to be essential for Brucella infection of other cell types (Keriel et al, 2015). CD98hc (SLC3A2) is a surface glycoprotein mediating amino-acid transport, regulation of integrin-dependent signalling and cell fusion (Nguyen & Merlin, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…Recent studies have identified some new players such as the flagellum-like structure, the transporter-like protein BacA and phosphatidylcholine required for intracellular survival within host cells (Roop et al, 2009 ). In addition to Brucella T4SS, the CD98hc transmembrane protein is recognized as essential for intracellular proliferation and modulates different signaling pathways (Keriel et al, 2015 ).…”
Section: Brucella Pathogenesismentioning
confidence: 99%
“…2 and Table S1). Among all these factors we can highlight the Ras related protein RAB7A, which is needed for Brucella trafficking to the replicative niche (10), the small GTPases RAC1 and CDC42, which are involved in Brucella internalization into non-phagocytic cells (13) as well as the transmembrane glycoprotein SLC3A2 (CD98hc), involved in both bacterial uptake and intracellular multiplication (28). Since the role of these individual components has already been described in the context of Brucella infection, they can be considered as benchmark to our results, and globally validate our systems-level perspective of the human infectome for Brucella infection.…”
Section: Resultsmentioning
confidence: 99%
“…Clusters with common predicted cellular function are colored and their prominent function are indicated. Hits previously reported to be involved in Brucella pathogenicity are highlighted: ARPC3 (29); TGFBR2 (22); SEC61G and TMED2 (35); RAC1 and CDC42 (13); SLC3A2 (28); RAB7A (10); SYK (63); ULK1 (64); For clarity, disconnected components are not displayed. The complete list of down- and up-hits is presented in Tables S1-S2.…”
Section: Resultsmentioning
confidence: 99%